Nilai Ajaran Agama Hindu Dalam Upacara Ngaturang Idangan - Kusuma Dhana, I Gusti Made; Yuliani, Ni Made; Sariyani, Ni Nyoman; Arlinayanti, Kadek Dwi; Hartaka, I Made (Jayapangus Press, 2023)
Hindus, especially in Bali, cannot be separated from ritual activities or yadnya ceremonies. Ritual activities have become the breath of life for the Hindu community, especially in Bali which has been passed down from generation to generation, where one of them is the Ngaturang Idangan Ceremony. The research objective was to find out the value of Hindu religious education in the Ngaturang Idangan Ceremony. The method used is qualitative research. Data collection uses non-participant observation techniques, unstructured interview techniques, document study techniques, and literature study techniques. The results of this study are that the reason for carrying out this ceremony is due to theological reasons, mythological reasons, philosophical reasons, and sociological reasons. The process of carrying out this ceremony can be divided into four stages, namely the preparatory stage, the initial stage, the core stage, and the final stage. The value of Hindu religious education contained in the implementation of the Ngaturang Idangan Ceremony includes the value of tattwa education, the value of moral education, the value of ceremonial education, the educational value of tat twam asi, and the educational value of tri hita karana.